(3TQM GdTaG HJYQja Mbhb GdeUWais - (3GdgQhj, GdbGQj, CHh GdMSf, fhQ GdOjf (B- (3GdeqdG, Ydj Hf (B((3SdWGf(B) (3eMeO, (B1014 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj CfRd GdbQBf CeG HYO ajbhd CabQ GdYHGO Edi cQe QHg GdHGQj Ydj Hf SdWGf eMeO GdbGQj Efj QCjJ cJGH GdTaG aj TeGFd UGMH GdGUWaG CLeY eG Ufa aj HGHg eLedGbUOJ Edi Cf CNOeg HTQM HYV eG jJYdb Hgs
(3BNQgG (B:s
(3fGbU GdBNQ hjfJgj YfO bhdg aLdO Cj GdTGJe KeGfjf LdOI hMdb QCSg Cj JYRjQG Cj JQcg, haj fSNI hSdeg ddMLGejf jYPHhfg HENQGL Oegs
(3aj HOGjI GdcJGH agQS ddCHhGH hGdehGVjY Vef LOhd ePgH, hVY GdeJf OGNd EWGQ ePgHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 5 / 12s
(3eYLe GdeDdajf(B: 2 / 446s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdJGQjNs